(untitled) (Información, cultura y sociedad, 2004)
The similarities and differences between thesauri and the lists of subject headings are analyzed, taking into account the work plan for the 2003 revision of the US standard Z39.19. This standard pretends to establish new guidelines for all types of controlled vocabulary in relation to their use with new technologies. We conclude that it is very important to review all the standards for controlled vocabulary, particularly those with international scope, but at the same time, it is necessary to be very careful in maintaining a rigorous control of terminology; a correct definition of hierarchical and associative relationships, and to promote the postcordination, managed, if possible, in faceted and computerized systems.